THE OPTION OF DECREASING COST BY ADVISABLE CARE OF TYRES - Vrabel, Jan; Sarkan, Branislav (Doprava a spoje, 2012)
This article discusses the effects of tyre and care of them on the costs of vehicle operations. The article is based on the facts that are supported by actual results from surveys. We try to accentuate the important factors which can be helpful for the user of the vehicle and also its operator, to reduce the overall costs associated with tyres.